Sintesis dan Karakterisasi Nanoselulosa Berbahan Serat Nanas sebagai Komponen Penguat Material Kedokteran Gigi - Angela Evelyna; Nalaria Prakusya; Dicky Juniata Dwi Suprana; Aulia Nur Ariswari; Bambang Sunendar Purwasasmita (Jurnal Material Kedokteran Gigi, 2019)
The ideal requirements of dental materials are biocompatibility and good mechanical properties for at least similar to human tooth tissue. Nanocellulose based on pineapple fibre is natural material that can be use to improve mechanical properties. Nano-size cellulose particles can be synthesize using Hummer’s modification method but need to test the microstructure characteristic. The objective of this study is to synthesize and characterize nanocellulose based on pineapple fibre using X-Ray Diffraction (XRD) and Transmission Electron Microscope (TEM). This study is an qualitative experimental laboratories study. Nanocelulose gel synthesized from pineapple fibre tested using Transmission Electron Microscopy (TEM) to observe its microstructure. Nanocellulose powder tested using X-Ray Diffraction (XRD) to observe its phase and crystallinity. Characterisation test result using XRD shows formation of cellulose from pineapple fibre with Hummer’s modification method. TEM result show cellulose formed in nano size and show nano-whisker pattern morphology. Nanocellulose synthesize based on pineapple fibre can be done using Hummer’s modification method. This result raising expectation of improving mechanical properties of dental materials.